MEASURING ADMINISTRATIVE SKILLS IN PUBLIC TERTIARY INSTITUTIONS IN CROSS RIVER STATE: IMPLICATIONS FOR EFFECTIVE GOVERNANCE AND SERVICE DELIVERY (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
The quality of governance and the service outcome greatly depends on the administrative structure of the public tertiary institutions. This paper will discuss the measurement of administrative capabilities among the staffs in the Cross River State tertiary institutions in Nigeria and the implications they have on good governance and service delivery. The study checks the competencies of administrators, finds the lack of skills in professional teams, using a mixed research methodology and evaluates their influence on performance at the institution. The results indicate inadequacy in the strategic planning, communication, and technological expertise that weakens the efficiency of governance and quality of services. The paper brings to the fore the academic issue of inadequate frameworks of measuring administrative competencies as well as the political issue of bureaucratic opposition to skill development programs. The study will integrate these gaps; hence, offering capacity building strategies and policy reform options to improve institutional effectiveness. The implications reiterate the fact that there is a need to develop targeted training and collaboration among stakeholders in order to enhance sustainable governance in tertiary institutions.